Implementasi Hak dan Kewajiban Keluarga Santri Tebuireng Perspektif Kitab Ḍaw’ al-Miṣbāḥ fī Bayān Aḥkām al-Nikāḥ - Ahmadi, Moh; Sukardi, Imam (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
Fulfillment of rights and obligations has been taught by scholars and exemplified in today's life. What about the students? The author wants to see the implementation of rights and obligations in the santri family at the Tebuireng Islamic boarding school. In this study the researcher used a qualitative research type with a library research type, which in this case used the book Ḍaw' al-Miṣbāḥ fī Bayān Aḥkām al-Nikāḥ. The results of this study the researchers found that the wife's rights mentioned by KH. M. Hasyim Asy'ari as a whole is also implemented by the Tebuireng Islamic Boarding School students' family, it's just that KH. M. Hasyim Asy'ari did not mention the housing (place of residence) clearly, but researchers interpreted the need for housing to be included in the point of subsistence. As for the husband's rights, there are several points mentioned by KH. M. Hasyim Asy'ari in accordance with what was applied by the resource persons, on the other hand there were several points not mentioned by the sources. This can show that the Tebuireng Islamic Boarding School students have implemented the teachings of KH. M. Hasyim Asy'ari in the book Ḍaw' Al-Miṣbāḥ Fī Bayān Aḥkām Al-Nikāḥ although not in its entirety.